Acute Intestinal Obstruction Due to Ascariasis in a Child: A Case from a Resource Limited Setting - Andriani, Christin; Syamsul Munir, Awliya; Utami, Ni Made Dwiyathi (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Ascariasis remains a widespread and frequently undiagnosed condition, with most cases being asymptomatic. However, severe manifestations can result in total or partial intestinal obstruction. In resource-limited settings, diagnosis primarily depends on clinical presentation, stool examination, and basic radiographic imaging. Case: A three-year-old child from rural Southwest Sumba presented with vomiting, fever, abdominal pain, and constipation. Physical examination, faecal examination, and imaging revealed partial small bowel obstruction due to an Ascaris bolus, complicated by mild to moderate dehydration. Following conservative management including fluid resuscitation, NPO status, NGT insertion, and single dose albendazole, the patient passed numerous worms, improved clinically, and was discharged on day five. Discussion: This case report highlights the diagnostic and management challenges of a severe form of ascariasis that caused partial small bowel obstruction in a resource-limited setting. The patient's differential diagnoses included intussusception, mesenteric cyst, and abdominal tuberculosis. The patient presented with risk factors including young age, frequent barefoot contact with soil, poverty, residence in an area with limited access to water and healthcare, and a lack of participation in deworming programs. Through clinical assessment, the patient was successfully managed with conservative treatment and antihelminthic therapy. Conclusion: While small bowel obstruction presents a diagnostic challenge with a wide range of differential diagnoses, ascariasis offers distinct risk factors and can be readily confirmed with basic diagnostic tools. Ascariasis remains a significant public health issue, highlighting the urgent need for intensified community education on hygiene and improved public health infrastructure in Southwest Sumba.